Anastazy Synaita, Homilia na temat Psalmu VI - Piasecki, Dariusz (Vox Patrum, 2023)
Anastasius of Synai’s homily on Psalm VI is maintained in the convention of Christian pedagogy. The preacher reminds his listeners of sin, encourages them to repent. This process is accompanied by conscious work on flaws, often tears of regret and improvement of life and repair of broken relationships with God and people. The fruit of spiritual effort understood in this way is the complete conversion of the sinner, forgiveness of sins and preparation for death, which is an inevitable stage towards eternal life.